Resolusi Konflik Berbasis Masjid dalam Sengketa Pembangunan Bandara Internasional di Yogyakarta - Ahmad Sihabul Millah (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
This research revealed how mosque-based conflict resolution was in disputes over the construction of an international airport in Yogyakarta. The research method used qualitative research with case study, while data collection techniques used interviews, observation, and documentation. The research results showed that the Al Hidayah Mosque in Kulonprogo Regency Yogyakarta was located on land that would be used as an airport. Aside from being a place of worship, the mosque also functions as a post for the people's movement against the government's demolition of houses, land, and places of worship (mosques) to build an airport. However, there were attempts by both parties to find a conflict resolution in resolving the issue. This means that the mosque was originally used as a place of conflict, but with various dynamics it had become a vehicle for conflict resolution between the community and the government in disputes over the construction of airports.